DNA polymerase alpha is associated with replicating SV40 nucleoprotein complexes. - Otto, B (1978)
Simian virus 40 (SV40) nucleoprotein complexes were extracted from nuclei of infected monkey cells and fractionated on neutral sucrose density gradients. Complexes which contained replicating SV40 DNA (95S) separated well from those containing closed circular supercoiled viral DNA (75S). DNA polymerase activity was associated with the replicating nucleoprotein complexes but not with the slower sedimenting complexes. This DNA polymerase activity coprecipitated with the nucleoprotein complexes in the presence of MgCl2 and remained associated with the 95S complexes. This DNA polymerase activity has been identified as primarily DNA polymerase alpha on the basis of its sedimentation behavior, optimum salt concentration, and sensitivity to N-ethylmaleimide. DNA polymerase gamma activity was also detected in the complexes, but DNA polymerase beta was not associated with the complexes.